Structure of Assets and Liabilities of Non-financial Corporations by Selected NACE Sections - Zawadzka, Agnieszka; Szmit, Kornelia (Olsztyn Economic Journal, 2022)
Experience from nations with established market economies demonstrates that small and medium-sized businesses are more inventive and able to respond to client demands and needs more quickly than giant businesses. Many publications produced by the EU institutions emphasize their crucial function. Small- and medium-sized enterprises (SMEs) reflect a society's entrepreneurial spirit and a sign of healthy competition in every economy. However, these businesses have numerous growth constraints in a setting that is changing quickly. At first, it is not simple. Due to the higher risk that start-ups face compared to larger corporations, they have difficulty obtaining funding from traditional sources and SME enterprises experience an equity gap. As a result, having access to finance has become crucial to expanding and competing in a particular market. In accordance with the accepted legal norms, the receiver is required to comply with the conditions set forth by the capital donor-recipient to be able to access external sources. One of the most significant influences on a company's ability to fulfil current obligations in full and generate adequate financial results is adherence to the fundamentals of asset financing, which highlight, among other things, the structural relationships in a company's balance sheet. The purpose of the analysis presented in this text is to identify differences in the structure of assets and liabilities between selected NACE sections of non-financial corporations in 2021 year. All analysed assets and liabilities are characterized by very strong asymmetry. Therefore, the outlier effect has been standardized using Weber median. Further statistical analyses used Kruskal-Wallis non-parametric ANOVA test to determine the similarity between assets and liabilities of selected NACE sections. The analysis showed that there are no significant differences in the assets and liabilities of the different NACE sections. The PROFIT analysis allowed for a graphical representation of the structure of the similarities between the NACE sections analysed and their arrangement due to the intensity of the assets and liabilities. As regards the NACE sections analysed, three homogeneous groups can be distinguished, of which industry and trade constitute two of them and the others - the third. It has been shown that the industry section is characterized by the highest intensity in both assets and liabilities.